2013
DOI: 10.1016/j.contraception.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in men's knowledge and attitudes about contraception

Abstract: Background Little is known about racial/ethnic differences in men’s contraceptive knowledge and attitudes. Study Design We used multivariable logistic regression to examine racial/ethnic differences in contraceptive knowledge and attitudes among 903 men aged 18–29 in the 2009 National Survey of Reproductive and Contraceptive Knowledge. Results Black and Hispanic men were less likely than whites to have heard of most contraceptive methods, including female and male sterilization, and also had lower knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…Objective contraceptive knowledge was measured based on a series of true/false statements assessing understanding of correct use, effectiveness and other facts about birth control pills, condoms, injectable contraception, and IUDs. These questions have been used in several other analyses of men's and women's contraceptive awareness and knowledge [14][15][16]22,24]. Four summary knowledge scores were calculated for each method based on the number of correct answers to these questions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Objective contraceptive knowledge was measured based on a series of true/false statements assessing understanding of correct use, effectiveness and other facts about birth control pills, condoms, injectable contraception, and IUDs. These questions have been used in several other analyses of men's and women's contraceptive awareness and knowledge [14][15][16]22,24]. Four summary knowledge scores were calculated for each method based on the number of correct answers to these questions.…”
Section: Methodsmentioning
confidence: 99%
“…While men may play an important role in promoting or discouraging contraceptive use, very little research has examined men's knowledge of and attitudes toward IUDs. Research has shown low levels of IUD knowledge among men, which may inhibit men's participation in decision-making [8][9][10]12,14,15]. One recent study that specifically examined knowledge and use of IUDs found that men were far more likely to have low IUD knowledge than women [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has documented that Black and Hispanic women have lower awareness of the full range of available contraceptive methods and also have lower levels of knowledge about the safety and efficacy of hormonal contraception compared to White women [1519]. Thus, racial/ethnic disparities in contraceptive knowledge may play an important role in differential contraceptive use patterns [17, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Both qualitative and quantitative data demonstrate that there are significant gaps in young men’s knowledge about contraception, and that knowledge deficits may be particularly pronounced among men from racial/ethnic minority groups [12]. The literature also suggests that both structured sex education and parent-child communication about sexual health increases contraceptive knowledge and use [37].…”
Section: Introductionmentioning
confidence: 99%